Public Evaluation Of Historical Building Facades In The Vicinity Of Dataran Merdeka, Kuala Lumpur - Askari, Amir Hossein (2009)

(untitled)
Historical district is an important element of city image content. Among the visual elements of a historical district, the building façade is an important element in representing the architectural features. Building façade is mostly the matter of evaluation to portray the visual characteristics of an environment. Therefore, giving attention and imposing sensitivity to the evaluation of building facades in a historical district directly influence the historical images. A historical area adjacent to Dataran Merdeka, located in Kuala Lumpur city, was chosen as the study area. The issue is focussed on the lack of harmony among the shapes, colours, decorations, and architectural styles of the historical building facades which have influenced the historical images in the study area. This inconsistency is in contrast with the Kuala Lumpur Structure Plan 2020 visions, which emphasizes on creating strong images for all the districts in Kuala Lumpur city. Thus, to deal with the stated issue, the main objective of the study was to investigate the building facades which represented the historical images of the study area based on the public‘s evaluation. The second objective was to investigate the architectural elements and characteristics which influence the public’s evaluation of the historical images of the building facades in the study area. The third objective was to identify the visual elements which influence the historical images of the building facades in the study area based on the public’s evaluation. Finally, the research tried to explore the urban elements which influence the historical images of the building facades in the study area based on the public’s evaluation. A quantitative method was used to achieve the objectives of the study. In this line, a questionnaire-based survey was chosen as a data collection instrument. The research participants chosen were visitors who are familiar with the area, and willing to answer the questions. Data analysis was carried out using both the content analysis and inferential analysis. The results suggested that the facades, with the highest mean scores, were considered as strongly representing the historical images and these include harmonious arches, columns, pilasters, ornament, and bright-coloured materials. Cleanliness, the use of appropriately architectural details, legibility, coherence, and the harmonious repetition of the elements were identified as the other factors which also improved the historical images of the facades. Moreover, the results also denoted the architectural style, colour, shape and material of the facades as the architectural elements, and the harmony between historical and modern buildings and street furniture as urban elements which influenced the evaluations of the historical building façade images. The findings of the study assist urban designers and planners to consider the importance of people’s evaluation of historical building facades.